SISTEM PEMANTAU SUHU DAN KELEMBABAN PADA GUDANG TEMBAKAU PR TUNAS MANDIRI BERBASIS INTERNET OF THINGS (IoT) - Yulis Yuana Cahyaning; Fachrudin Hunaini (JASEE Journal of Application and Science on Electrical Engineering, 2025)
The tobacco processing industry has a large economic impact. In the process of storing tobacco, it is necessary to pay attention to the temperature and humidity conditions of the room. The process of monitoring the storage room will be difficult if the manager is outside the industrial environment. Therefore, an Internet of Things-based room temperature and humidity monitoring system was created using Wemos D1 as a controller, the Blynk Application interface and real-time Telegram notifications. The Blynk application can monitor all the latest information and set the temperature and humidity set points of the device. The Telegram bot can provide notification information if the temperature and humidity set points are not appropriate. The manager can immediately take effective action based on information from the emergency warning system.